2017
DOI: 10.1037/ort0000285
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and symptoms of obsessive–compulsive disorder among African Americans.

Abstract: This study examined symptoms of obsessive-compulsive disorder (OCD) in a nationally-representative sample of African American adults (n = 3,570), and correlations between OCD symptom dimensions and experiences of discrimination. Two categories of discrimination were examined, everyday racial discrimination and everyday non-racial discrimination (e.g., due to gender, age, and weight) to determine if racial discrimination had a unique impact on OCD symptoms. Results indicated that everyday racial discrimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Although questioned by Lilienfeld, microaggressions and the largely overlapping construct termed everyday racial discrimination are in fact associated with many negative mental-health consequences, including stress (Torres, Driscoll, & Burrow, 2010), anxiety (Banks et al, 2006; Blume et al, 2012), depression (Huynh, 2012; Nadal, Griffin, Wong, Hamit, & Rasmus, 2014), symptoms of posttraumatic stress disorder (Williams, Printz, & DeLapp, 2018), low self-esteem (Nadal, Wong, Griffin, Davidoff, & Sriken, 2014; Thai et al, 2017), obsessive-compulsive disorder (Williams et al, 2017), substance use (T. T. Clark, Salas-Wright, Vaughn, & Whitfield, 2015; Gerrard et al, 2012), alcohol abuse (Blume, Lovato, Thyken, & Denny, 2012), severe psychological distress (Banks et al, 2006; Hurd, Varner, Caldwell, & Zimmerman, 2014), reduced self-efficacy (Forrest-Bank & Jenson, 2015), and suicide (Hollingsworth et al, 2017; O’Keefe, Wingate, Cole, Hollingsworth, & Tucker, 2015).…”
Section: Microaggressions Exert An Adverse Impact On Mental Healthmentioning
confidence: 99%
“…Although questioned by Lilienfeld, microaggressions and the largely overlapping construct termed everyday racial discrimination are in fact associated with many negative mental-health consequences, including stress (Torres, Driscoll, & Burrow, 2010), anxiety (Banks et al, 2006; Blume et al, 2012), depression (Huynh, 2012; Nadal, Griffin, Wong, Hamit, & Rasmus, 2014), symptoms of posttraumatic stress disorder (Williams, Printz, & DeLapp, 2018), low self-esteem (Nadal, Wong, Griffin, Davidoff, & Sriken, 2014; Thai et al, 2017), obsessive-compulsive disorder (Williams et al, 2017), substance use (T. T. Clark, Salas-Wright, Vaughn, & Whitfield, 2015; Gerrard et al, 2012), alcohol abuse (Blume, Lovato, Thyken, & Denny, 2012), severe psychological distress (Banks et al, 2006; Hurd, Varner, Caldwell, & Zimmerman, 2014), reduced self-efficacy (Forrest-Bank & Jenson, 2015), and suicide (Hollingsworth et al, 2017; O’Keefe, Wingate, Cole, Hollingsworth, & Tucker, 2015).…”
Section: Microaggressions Exert An Adverse Impact On Mental Healthmentioning
confidence: 99%
“…These findings suggest that amplified views about the importance of cleanliness among African Americans may function to compensate for negative stereotypes about African Americans. Williams et al (2017e) also found that African Americans who report everyday racial discrimination are more likely to experience contamination obsessions, as well as unacceptable thoughts obsessions. African Americans may also be hesitant to disclose sexual or aggressive obsessions for fear of validating false racial stereotypes of being sexually deviant or violent (Williams et al, 2017c).…”
Section: Stigma and Oppression Embedded In Obsessional Concernsmentioning
confidence: 84%
“…Williams et al (2014) also detail how clinicians can provide psychoeducation about how racism may contribute to symptomatology (e.g. Williams et al, 2017e). Clients may further benefit from hearing examples of how treatment has benefited other minoritized clients with OCD (Williams et al, 2014).…”
Section: Integrating Clients' Perspectives and Preferences Into Treatmentioning
confidence: 99%
“…Data suggest that due to perceptions of discrimination, many BIPOC individuals go so far as to delay, avoid seeking, or prematurely discontinue health care. [150][151][152][153] Again, BIPOC patients' access to adequate medical treatment becomes compromised, potentially resulting in increased morbidity and even mortality.…”
Section: Dovepressmentioning
confidence: 99%